Pendidikan jasmani dan pendidikan kesihatan persepsi dan sikap pelajar di Sekolah Menengah daerah Kuala Muda, Kedah - Thanabal, Desen (2008)
The purpose of this study was to determine student's perception and attitude towards implementation of teaching and learning Physical and Health Education in schools. This study also investigates the significant differences in perception and attitude among students towards the implementation of teaching and learning Physical and Health Education based on selected demographic factors. The study then, sought to identify the relationship between student's perception and attitude and the following factors : teachers, teaching period and equipment and facilities in schools. The sample chosen for this study consists of 360 Form Four student from 10 secondary schools in Kuala Muda, District of Kedah. The questionnaire has three section. Section A is composed of 6 questions related to demographic characteristic of the student. Section B is compose of 13 questions to assess the perception and attitude of the students. Section C consists of 27 question to determine the factors that influence perception and attitude of students towards implementation of teaching and learning Physical and Health Education was moderately high. Secondly, &Test and One-Way Analysis of Variance results showed that there were no significant differences in students' perception and attitude based on students' race, but significant differences in students' perception and attitude based on students' race, but significant differences based on gender and school-stream. Thirdly, correlation analysis showed that factors such as teachers, teaching period and equipment and facilities had a significant positive relation between a student's perception and attitude towards implementation of teaching and learning Physical and Health Education in school. Finally recommendations for policy makers, program planners and researchers were made.